CAUCHEMARS CULINAIRES, NAUSÉE NARRATIVE LES ENJEUX ESTHÉTIQUES DE LA RÉTROSPECTION - Barnett, Richard-Laurent (Revista Letras, 2003)
The essay tackles a tripartite phenomenon: 1) the ways in which la gastronomie, as a generative cipher of societal norms and cultural prerogatives, has evolved from the 19th to the 20th century; 2) the residual effects of this evolution or difference, which, in the sphere of textuality, largely over-determines poetic and narrative structures in literary works; and 3) the impact and consequences upon writers of the post-modern era as they come to grips with the paradoxes of contemporaneity and as they struggle to negotiate earlier texts.